Friedreich Ataxia: New Pathways - Pandolfo, Massimo (2012)
Friedreich ataxia is a rare disorder characterized by an autosomal recessive pattern of inheritance. The disease is noted for a constellation of clinical symptoms, notably loss of coordination and a variety of neurological and cardiac complications. More recently, scientists have focused their research on an array of general investigations of the underlying cellular basis for the disease, including mitochondrial biogenesis, iron-sulfur cluster synthesis, iron metabolism, antioxidant responses, and mitophagy. Combined with investigations that have explored the pathogenesis of the disease and the function of the protein frataxin, these studies have led to insights that will be key to identifying new therapeutic strategies for treating the disease.